A Co‐Doped MnO2 Catalyst for Li‐CO2 Batteries with Low Overpotential and Ultrahigh Cyclability. Issue 34 (3rd July 2019) - Ge, Bingcheng; Sun, Yong; Guo, Jianxin; Yan, Xiaobin; Fernandez, Carlos; Peng, Qiuming
Abstract: Li‐CO2 batteries can not only capture CO2 to solve the greenhouse effect but also serve as next‐generation energy storage devices on the merits of economical, environmentally‐friendly, and sustainable aspects. However, these batteries are suffering from two main drawbacks: high overpotential and poor cyclability, severely postponing the acceleration of their applications. Herein, a new Co‐doped alpha‐MnO2 nanowire catalyst is prepared for rechargeable Li‐CO2 batteries, which exhibits a high capacity (8160 mA h g −1 at a current density of 100 mA g −1 ), a low overpotential (≈0.73 V), and an ultrahigh cyclability (over 500 cycles at a current density of 100 mA g −1 ), exceeding those of Li‐CO2 batteries reported so far. The reaction mechanisms are interpreted depending on in situ experimental observations in combination with density functional theory calculations. The outstanding electrochemical properties are mostly associated with a high conductivity, a large fraction of hierarchical channels, and a unique Co interstitial doping, which might be of benefit for the diffusion of CO2, the reversibility of Li2 CO3 products, and the prohibition of side reactions between electrolyte and electrode. These results shed light on both CO2 fixation and new Li‐CO2 batteries for energy storage. Abstract : A Co‐doped alpha‐MnO2 nanowire catalyst for Li‐CO2 batteries is prepared, which shows a large capacity, a low overpotential, and ultrahigh cyclability. The reasons lie in three aspects: the good conductivity, the high catalytic activity, and the elimination of side reactions. The catalyst is highlighted by its simplicity and high‐yield production, which attributes to the development of Li‐CO2 batteries.